Genetic variation of giant freshwater prawns Macrobrachium rosenbergii wild population of South Sulawesi, Indonesia - WAHIDAH WAHIDAH; SHARIFUDDIN B. ANDY OMAR; DODY D. TRIJUNO; ESTU NUGROHO; AMRULLAH AMRULLAH; KHUSNUL KHATIMAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Wahidah, Omar SBA, Trijuno DD, Nugroho E, Amrullah, Khatimah K. 2023. Genetic variation of giant freshwater prawns Macrobrachium rosenbergii wild population of South Sulawesi, Indonesia. Biodiversitas 24: 3081-3090. Quality giant freshwater prawn broodstock can be provided using broodstock sources from wild populations with good morphological and genetic performance. This study aimed to analyze the genotypes of the wild population of giant freshwater prawns in South Sulawesi, hence it can be used as basic information for quality broodstock. Evaluation of giant prawn haplotypes, Macrobrachium rosenbergii, from 3 rivers in South Sulawesi: 26 samples from the Waelawi River (11 males, 15 females); 25 samples from the Kalibone River (10 males, 15 females); and 26 samples from the Kariango River (12 males, 14 females), so there are 6 population groups. Analysis used mt-DNA and obtained an amplification of 700 bp. The amplified restriction uses four enzymes (Hae III, Mbo I, Rsa I, and Taq I). The identified male and female Kariango populations each had 3 haplotypes: female Kalibone had 2 haplotypes; male and female Waelawi had 1 haplotype; and male Kalibone had 1 haplotype. Female Kariango had the highest haplotype diversity (0.3651), followed by male Kariango (0.1449) and female Kalibone (0.1011). Kariango females have the farthest genetic distance from Kalibone males, Waelawi males, and Waelawi females. The male Waelawi, female Waelawi, and male Kalibone are in one cluster and form a new cluster with the male Kariango, then with the female Kalibone, and the last cluster is formed with the female Kariango. The Kariango female population can be used as potential broodstock, which can be mated with Kalibone males, Waelawi males, or other populations.